Hyperpolarized δ-[1- 13C]gluconolactone imaging visualizes response to TERT or GABPB1 targeting therapy for glioblastoma - Noriaki Minami; Donghyun Hong; Celine Taglang; Georgios Batsios; Anne Marie Gillespie; Pavithra Viswanath; Nicholas Stevers; Carter J. Barger; Joseph F. Costello; Sabrina M. Ronen (Scientific Reports, 2023)
Abstract TERT promoter mutations are a hallmark of glioblastoma (GBM). Accordingly, TERT and GABPB1, a subunit of the upstream mutant TERT promoter transcription factor GABP, are being considered as promising therapeutic targets in GBM. We recently reported that the expression of TERT or GABP1 modulates flux via the pentose phosphate pathway (PPP). Here, we investigated whether 13C magnetic resonance spectroscopy (MRS) of hyperpolarized (HP) δ- [1-13C]gluconolactone can serve to image the reduction in PPP flux following TERT or GABPB1 silencing. We investigated two different human GBM cell lines stably expressing shRNAs targeting TERT or GABPB1, as well as doxycycline-inducible shTERT or shGABPB1cells. MRS studies were performed on live cells and in vivo tumors, and dynamic sets of 13C MR spectra were acquired following injection of HP δ-[1-13C]gluconolactone. HP 6-phosphogluconolactone (6PG), the product of δ-[1-13C]gluconolactone via the PPP, was significantly reduced in TERT or GABPB1-silenced cells or tumors compared to controls in all our models. Furthermore, a positive correlation between TERT expression and 6PG levels was observed. Our data indicate that HP δ-[1-13C]gluconolactone, an imaging tool with translational potential, could serve to monitor TERT expression and its silencing with therapies that target either TERT or GABPB1 in mutant TERT promoter GBM patients.